2018
DOI: 10.1371/journal.pone.0202969
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-specific impairment among older people. An investigation using both sensory thresholds and subjective measures across the five senses

Abstract: Age-related sensory impairment is a slow and gradual progress, which affects multiple modalities. Two contradictory hypotheses exist about the age-related decline of sensory thresholds. The common factor theory assumes one underlying factor—which accounts for the loss of several sensory modalities simultaneously—and the specific factor theory predicts that the sensory decline is uncorrelated between different modalities. In this study, we aimed to explore whether (i) there is a common factor of sensory thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 72 publications
6
86
0
2
Order By: Relevance
“…In the review undertaken on this topic by Sergi, et al [ 58 ], the authors concluded that there was only sufficient evidence to conclude an age-related decrease in the perception of bitter (PROP) and sour tastes and that more studies were required to clearly conclude the decrease in the perception of other tastes. Our study, therefore, is useful in that it provides more specific data on quantification and better characterization of the decrease in the perception of the different tastes with age; other studies have analysed fewer taste qualities [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ] have focused on a shorter age range [ 64 , 65 ], have studied children and their mothers [ 65 ]; or when the five taste qualities have been studied, their sample size has been very small [ 38 , 58 , 66 ]. Therefore, the results of these individual studies regarding the association between taste perception qualities and age have been heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In the review undertaken on this topic by Sergi, et al [ 58 ], the authors concluded that there was only sufficient evidence to conclude an age-related decrease in the perception of bitter (PROP) and sour tastes and that more studies were required to clearly conclude the decrease in the perception of other tastes. Our study, therefore, is useful in that it provides more specific data on quantification and better characterization of the decrease in the perception of the different tastes with age; other studies have analysed fewer taste qualities [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ] have focused on a shorter age range [ 64 , 65 ], have studied children and their mothers [ 65 ]; or when the five taste qualities have been studied, their sample size has been very small [ 38 , 58 , 66 ]. Therefore, the results of these individual studies regarding the association between taste perception qualities and age have been heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the older person's thermal perception of the environment is 'blunted' is consistent with the biological consequences of ageing on thermogenesis and decline in thermosensitivity [35]. This blunting of thermal sensation can occur similarly as in other types of sensory perception loss wih age [36];…”
Section: Discussionmentioning
confidence: 56%
“…The possibility that the older person’s thermal perception of the environment is ‘blunted’ is consistent with the biological consequences of ageing on thermogenesis and decline in thermosensitivity [ 35 ]. This blunting of thermal sensation can occur similarly as in other types of sensory perception loss with age [ 36 ]; hearing, vision, taste and smell being additional examples. We have observed features of thermal blunting in the older residents, particularly those with dementia where we observed residents with low extremity (digit) temperatures corresponding to ‘cold hands’ reporting thermal sensation as neutral (or comfortable) even with obvious visual ‘thermal amputation’ on the thermal map and even where environmental temperature was within the thermoneutral range [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 92%